N-linked glycosylation of the West Nile virus envelope protein is not a requisite for avian virulence or vector competence. - Payal D Maharaj; Stanley A Langevin; Bethany G Bolling; Christy C Andrade; Xavier A Engle; Wanichaya N Ramey; Angela Bosco-Lauth; Richard A Bowen; Todd A Sanders; Claire Y-H Huang; William K Reisen; Aaron C Brault (Public Library of Science (PLoS), 2019)
The N-linked glycosylation motif at amino acid position 154-156 of the envelope (E) protein of West Nile virus (WNV) is linked to enhanced murine neuroinvasiveness, avian pathogenicity and vector competence. Naturally occurring isolates with altered E protein glycosylation patterns have been observed in WNV isolates; however, the specific effects of these polymorphisms on avian host pathogenesis and vector competence have not been investigated before. In the present study, amino acid polymorphisms, NYT, NYP, NYF, SYP, SYS, KYS and deletion (A'DEL), were reverse engineered into a parental WNV (NYS) cDNA infectious clone to generate WNV glycosylation mutant viruses. These WNV glycosylation mutant viruses were characterized for in vitro growth, pH-sensitivity, temperature-sensitivity and host competence in American crows (AMCR), house sparrows (HOSP) and Culex quinquefasciatus. The NYS and NYT glycosylated viruses showed higher viral replication, and lower pH and temperature sensitivity than NYP, NYF, SYP, SYS, KYS and A'DEL viruses in vitro. Interestingly, in vivo results demonstrated asymmetric effects in avian and mosquito competence that were independent of the E-protein glycosylation status. In AMCRs and HOSPs, all viruses showed comparable viremias with the exception of NYP and KYS viruses that showed attenuated phenotypes. Only NYP showed reduced vector competence in both Cx. quinquefasciatus and Cx. tarsalis. Glycosylated NYT exhibited similar avian virulence properties as NYS, but resulted in higher mosquito oral infectivity than glycosylated NYS and nonglycosylated, NYP, NYF, SYP and KYS mutants. These data demonstrated that amino acid polymorphisms at E154/156 dictate differential avian host and vector competence phenotypes independent of E-protein glycosylation status.